Learning independence: The influence of parental social support and self-regulation - Yulianingsih, Tri; Fathiyah, Kartika Nur (Universitas Negeri Yogyakarta, 2025)
Low parental support and learning attitudes can hinder students' learning processes. This study was conducted to determine the effect of parental social support and self-regulation on the learning independence of fifth-grade students at Fostered Area (Dabin) Elementary School 1, Prambanan District. This study uses a quantitative research type of ex post facto design without providing special treatment to students based on the research instruments created. The population in this study amounted to 122 students, with a research sample of 92 students selected randomly. The research instruments used were in the form of a questionnaire on parental social support, a questionnaire on self-regulation, and a questionnaire on learning independence, which have been proven valid by expert judgment, a validity test, and a reliability test. The tabulated data were subjected to assumption tests in the form of a one-sample Kolmogorov-Smirnov normality test, linearity test, multicollinearity test, and heteroscedasticity test with the help of SPSS 29. Furthermore, the data were analyzed using multiple regression techniques with the help of SPSS version 29 to test the research hypothesis. The results of the study prove that: 1) Parental social support and self-regulation together influence students' learning independence. 2) Parental social support partially influences students' learning independence. 3) Self-regulation partially influences students' learning independence in class V of Fostered Area (Dabin) Elementary School, Prambanan District. So, it can be concluded that parental social support and self-regulation have implications for learning independence. It is hoped that this study can contribute to increasing the role of parents in providing social support to their children. It is recommended that future studies examine interventions or programs designed to enhance self-regulation and learning independence while taking into account the role of social support, particularly from parents.